The phenomenon of poverty in the Mamluk era through the book of Ahmed bin Ali Al-Dalji Al-Falaqa and Al-Falakun 770-838 AH / 1369-1435 AD - طالب مران; محسن يونس; أحمد الحميد العنزي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study aims to show the extent to which historians of the Mamluk era monitor the details of the aspects of social activity and its categories and the interaction between them, and the reflection of this interaction on the reality of political, economic and intellectual life in the Mamluk era by studying the scientific material mentioned by Ahmed bin Ali to Delji in his book Al-Falaqa and Al-Maflokoun, in which its owner Al-Dalji deals with A clear phenomenon in the Egyptian and Shami society that affected the reality of social life and was a reflection of the economic life of this group, indicating the factors, manifestations and results related to the phenomenon of poverty, to which multiple political, military, economic and natural factors contributed, which prompted some of the owners of this category to take various methods and ways to obtain money and secure A life in which he lives in luxury, and compares what he mentioned in his book with the rest of the sources of his time in their monitoring of the reality of living life. The research will depend on collecting scientific material from Arabic sources, references, and articles related to poverty, then working on formulating information extracted from sources and references according to the scientific historical analysis method, whether analyzing the opinions of historians who wrote books on this subject or analyzing historical events in approved sources that serve search.